Modeling a Microstretch Thermoelastic Body with Two Temperatures. (14th November 2013) - Marin, M.; Agarwal, R. P.; Mahmoud, S. R.
Abstract : We consider a theory of thermoelasticity constructed by taking into account the heat conduction in deformable bodies which depends on two temperatures. The first one is the conductive temperature, the second is the thermodynamic temperature, and the difference between them is proportional to the heat supply.